Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Design and development of trivalent aluminum ions induced self healing polyacrylic acid novel hydrogels - Anjum, Sadiya; Gurave, Pramod; Badiger, Manohar V.; Tiwari, Neha; Gupta, Bhuvanesh (POLYMER, 2017)
Development of ionically crosslinked superabsorbent polyacrylic acid (PAA) self-healing hydrogels using trivalent aluminum ions was investigated. The PAA hydrogels exhibited excellent self-healing behavior depending on the amount of the aluminum within the matrix. The migration of these ions within the polymer matrix was responsible for the physical crosslinking of the hydrogel and the origin of self healing ability. The PAA-Al hydrogels were insoluble in water and exhibited significantly high degree of swelling (similar to 4000%). Hydrogel also exhibited good mechanical properties with high level of elongation. Excellent self-healing efficiency was observed under dynamic as well as oscillatory Theological measurements. The presence of Al ions within PAA hydrogel facilitated the self-healing ability because of the ionic interaction in these gels which plays the key role of dynamic reversible sacrificial bonds which reforms upon reversal of the deformative force. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Aluminum chloride; Behavior; Complex; Composite; crosslinking; Delivery; High-Mechanical Strength; hydrogels; Network; Polyacrylic acid; Polymeric Materials; Self-healing; swelling; Tough; pH